2009
DOI: 10.1007/978-3-642-03887-7_22
|View full text |Cite
|
Sign up to set email alerts
|

QCM Based on Flow System for Cardiovascular Disease

Abstract: Abstract-Quartz Crystal Microbalance (QCM) is a special sensor which has acoustic impedance detector by mass loading. In this study Cardiac Troponin T (CTnT) which elevates in all patients with AMI diagnosed by World Heath Organization (WHO) criteria is used as immunoligical assay onto sensor. Detection of the Troponin T is developed based on antigenantibody system on QCM sensor as solid support and signal transduction for immobilization to monitor risk marker of myocardial infarction. To immobilize antibody, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“… 33 The laboratory diagnosis of biomarkers associated with various diseases is one of the main areas for the development of various types of sensors including electrochemical, 34 optical, 35 and quartz crystal microbalance sensors. 36 Various bioreceptors including proteins, small molecules, and nucleic acids are efficacious bioreceptors for increasing the selectivity and sensitivity of sensors. Among the different types of bioreceptors, antibodies represent an important type of detection marker for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“… 33 The laboratory diagnosis of biomarkers associated with various diseases is one of the main areas for the development of various types of sensors including electrochemical, 34 optical, 35 and quartz crystal microbalance sensors. 36 Various bioreceptors including proteins, small molecules, and nucleic acids are efficacious bioreceptors for increasing the selectivity and sensitivity of sensors. Among the different types of bioreceptors, antibodies represent an important type of detection marker for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…This modification improved the sensitivity of the QCM biosensor compared with an uncoated surface. They observed that the frequency shift was directly proportional to the troponin T concentration, and the biosensor achieved an LOD of 5 ng/mL . This study demonstrates the potential of QCM biosensors in the sensitive detection of troponin T, a key cardiac biomarker used in diagnosing heart-related conditions.…”
Section: Biosensorsmentioning
confidence: 61%
“…This can then be detected using magneto-resistive sensor to measure the amount of target analyte in the sample. Acoustic biosensor is based on mass of captured analyte on a surface of the sensor [9][10]. The surface of the sensor is coated with immobilized agent to the target analyte.…”
Section: B Sensorsmentioning
confidence: 99%